CLINICAL CASE OF RESUMPTION OF ANTICOAGULANT THERAPY AFTER IMPLANTATION OF THE AMPLATZER CARDIAC PLUG LEFT ATRIAL APPENDAGE OCCLUDER - R. V. Guchaev; D. V. Pevzner; E. V. Merkulov; M. I. Makeev; N. S. Zhukova; R. M. Shakhnovich; T. Yu. Vedenikin; N. V. Shestakova («REMEDIUM GROUP» Ltd., 2019)
The article demonstrates a clinical case of forced renewal of anticoagulant therapy after the endovascular closure of the left atrial appendage. Patient with atrial fibrillation and high risk of thromboembolic complications and bleeding on the background of warfarin administration and inappropriate INR values had an acute hemorrhagic cerebral blood flow disorder developed. Endovascular closure of the left atrial appendage was performed. However, the thrombosis of the area of the delivery system fastening revealed after 12 months was an indication for the resumption of anticoagulant therapy.The article presents modern data on the use of occluders for closing the left atrial appendage, the frequency of complications and antiplatelet therapy schemes depending on the presence of thrombosis risk factors and bleeding.